THE ROLE OF SHADE-GROWN COFFEE AGROFORESTRY SYSTEMS IN CONSERVING BIRD DIVERSITY IN THE SUMATRAN HIGHLANDS - Regi Fernandez; Eddy Silamat; Caroline Eide (Yayasan Adra Karima Hubbi, 2025)
Conservation in the Sumatran Highlands is critically threatened by the continuous simplification of shade-grown coffee (SGC) agroforestry systems into sun-grown monocultures, necessitating an urgent evaluation of the ecological function of complex SGC structures. This study aimed to systematically quantify avian species richness (SR) and functional diversity (FDI) across the coffee land-use gradient to establish the specific structural determinants necessary for developing an Avian-Optimized Agroforestry Protocol (AOAP). A quantitative, gradient-based comparative study utilized the Fixed-Radius Point Count method and meticulous structural measurements across 54 plots. Data were analyzed using ANOVA and multiple linear regression. Results showed that High-Diversity SGC (HD-SGC) plots retained 72% of avian SR and maintained an FDI (4.1) statistically equivalent to natural forest fragments (4.8), proving their functional viability. Regression confirmed that Shade Tree Basal Area (BA) and Canopy Closure (CC) are the most significant positive predictors of bird diversity (R^2=0.78, p < 0.001). Simplified systems, conversely, registered a steep 40% drop in SR, confirming their ineffectiveness. The research concludes that the AOAP is validated by confirming that conservation value is determined by structural complexity, not just 'shade.' This compels global certification schemes to adopt precise, performance-based ecological standards using quantitative metrics like BA and CC.